2000
DOI: 10.1034/j.1600-0609.2000.065003195.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of soluble CD44 variant 6 are correlated with shorter survival in aggressive non‐Hodgkin's lymphoma

Abstract: A variant form of CD44 that has additional amino acids in the common protein backbone (CD44-v6) seems to play a role in the metastasis of malignancies. We measured soluble CD44-v6 (sCD44-v6) by ELISA in 201 patients with malignant lymphoma. The sCD44-v6 level was significantly elevated in patients with non-Hodgkin's lymphoma (NHL) (n = 184). The sCD44-v6 level was correlated significantly with the standard sCD44 and soluble interleukin-2 receptor levels, but only weakly with serum lactate dehydrogenase (LDH). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…For instance, in aggressive NHL patients, the p53 mutation, the nm23-HI protein, and serum soluble Fas level were associated with prognosis (Ichikawa et al 1997;Niitsu et al 1999;Hara et al 2000). Moreover, many prognostic factors such as basic fibroblast growth factor (Salven et al 1999), IL-6 (Preti et al 1997), IL-10 (Stasi et al 1994, soluble CD44 variant 6 (Sasaki and Niitsu 2000), and survivin (Adida et al 2000) have also been investigated. In addition, using gene expression analysis with DNA microarrays, DLBCL was recently classified into the two different groups of germinal center B-like DLBCL and activated B-like DLBCL.…”
Section: Discussionmentioning
confidence: 94%
“…For instance, in aggressive NHL patients, the p53 mutation, the nm23-HI protein, and serum soluble Fas level were associated with prognosis (Ichikawa et al 1997;Niitsu et al 1999;Hara et al 2000). Moreover, many prognostic factors such as basic fibroblast growth factor (Salven et al 1999), IL-6 (Preti et al 1997), IL-10 (Stasi et al 1994, soluble CD44 variant 6 (Sasaki and Niitsu 2000), and survivin (Adida et al 2000) have also been investigated. In addition, using gene expression analysis with DNA microarrays, DLBCL was recently classified into the two different groups of germinal center B-like DLBCL and activated B-like DLBCL.…”
Section: Discussionmentioning
confidence: 94%
“…The precise regulation of cell-cell and cell-matrix adhesion and control over lipid raft -associated signaling complexes play a crucial role in various aspects of normal T-cell biology, including T-cell homing, T-cell activation, and cell-cell contact formation with target cells (63,(81)(82)(83)(84)(85), whereas in malignant lymphocytes deregulation of these processes may result in increased invasiveness and aggressiveness (75)(76)(77)(78)(79)86). As T-ALLs are frequently highly invasive and in T lymphocytes integrin receptors of the h 1 class are responsible for both cell adhesion to the extracellular matrix component fibronectin and for cell-cell interactions through the cell-membrane ligand such as VCAM-1, our observations suggest that ephrin-B1 may play an important role in regulating the invasiveness of T-ALL cells through the negative control over their cell-cell and cell-matrix interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules regulating cell adhesion may play an important role in the invasiveness and aggressiveness of cancer cells (75)(76)(77)(78)(79). Because our experiments showed that ephrin-B1 suppresses attachment of T-ALL cells, we attempted to determine if ephrin-B1 also controls their invasive behavior.…”
Section: Ephrin-b Signaling Supports Invasiveness Of T-all Cellsmentioning
confidence: 99%
“…They are either constitutively expressed on the surface of peripheral lymphocytes (CD44s) or are induced upon antigen mediated activation (CD44v3 and CD44v6) (reviewed by Sneath and Mangham 7 ). CD44v are necessary for tumour spread and metastasis, and their expression is generally associated with an unfavourable prognosis [7][8][9][10][11][12][13][14][15][16] in DLBCL and in several other haematological malignancies, such as multiple myeloma, NHL, Hodgkin lymphoma, and acute myelogenous leukaemia. [13][14][15][16][17][18][19][20][21][22][23][24] "CD44 isoforms play a key role in lymphocyte migration, homing, and activation and participate in the transmission of signals that regulate haemopoiesis and apoptosis"…”
mentioning
confidence: 99%